Desenvolvimento de nanocompósito de poliamida 6 e óxido de grafeno e união com alumínio 6061 por sobremoldagem por injeção - Luiz, Giuliana De Mitri (2023)
Polymer-metal hybrid structures are presented as an alternative to the transportation industry, since they are able to combine high mechanical strength and lightness. The present study focuses on obtaining hybrid joints of polyamide 6 (PA6) and graphene oxide (GO) nanocomposite with aluminum alloy AA6061 through injection overmolding. GO was synthesized from pristine graphene using modified Hummers method and characterized by Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The PA6-GO nanocomposite (99.5/0.5 %) was prepared by melt mixing from a concentrate produced in a thermokinetic mixer (DRAIS), followed by dilution in a twin-screw extruder. The obtained material was injection molded into standard specimens for testing and analysis. SEM analysis showed the absence of GO clusters in PA6. Thermogravimetric analysis (TGA) demonstrated that the thermal stability of PA6 is not affected by the incorporation of GO. Differential scanning calorimetry (DSC) revealed that GO acts as a nucleating agent and reduces the crystallization rate of PA6. Mechanical tests showed that the addition of 0.5% GO provided a 21% increase in the elastic modulus and a 16% increase in the tensile strain, with an 81% reduction in strain at break and a 44% reduction in the IZOD impact strength. The metallic substrate AA6061 was laser-textured with grooves spaced by 100 μm, with a width of 56 ± 6 μm and a depth of 50 ± 5 μm, analyzed by confocal laser microscopy. Optical microscopy analysis of the cross-section of PA6/AA6061 and PA6-GO/AA6061 hybrid joints revealed complete polymer penetration into the metal cavities, resulting in good mechanical anchoring and shear strength of 8,3 ± 0,8 and 7,1 ± 1,7 MPa, respectively, with failure by delamination and polymer fracture. Fractured surfaces were analyzed by SEMEDS, where the presence of aluminum adhered to the polymer was observed, indicating cohesive joint failure.